Mechanical and thermal characterization of banana peel fibers/HDPE composites - Pereira, P. H.F. [UNESP]; Watashi, C. Y. [UNESP]; Brocks, T. [UNESP]; Benini, K. C.C.C. [UNESP]; Voorwald, H. J.C. [UNESP]; Cioffi, M. O.H. [UNESP] (My University, 2012)
Lignocellulosic fibers from banana peels were washed with water in order to increase its compatibility with polymeric matrix. These fibers were mixed with high density polyethylene (HDPE) and placed in an injector chamber in order to obtain specimens for tensile tests. Samples of HDPE/washed banana fibers composites were characterized by tensile tests and thermal analysis. Results showed that the addition of washed banana fibers decreased the thermal stability of composites; on the other hand increased the melting and crystallization temperatures of composites. The addition of 5% of fibers also provided an improvement in the mechanical properties of composites in comparison with the pure HDPE.
Keywords: And high density polyethylene; Peel banana fibers; Tensile tests; Thermogravimetric analysis